Developing cognitive processes in teenagers through the reading of short stories (2008)
This research-innovation project aims at developing cognitive processes explicitly through the reading of short stories. It is based on reading strategies and Bloom’s cognitive domain (1981) which was applied in the English classes we had with sixth graders at IPARM (Instituto Pedagógico Arturo Ramírez Montufar) School at Universidad Nacional de Colombia, in Bogotá. The six categories (knowledge, comprehension, application, analysis, synthesis and evaluation) of Bloom’s cognitive domain were worked with reading activities. In order to develop our students’ cognitive processes and their English language learning skills, it was first necessary to involve them in reading for pleasure. The findings are the result of triangulated data collected through teachers’ journals, direct observation, and students’ artifacts and show the evidence of the significant improvement students have made in their English language learning skills and cognitive processes. Key words: Cognitive processes, reading strategies, Bloom’s taxonomy, English language learning skills Este proyecto de investigación e innovación buscó desarrollar los procesos cognitivos de manera explícita a través de la lectura de historias cortas. Se basa en las estrategias de lectura y el dominio cognitivo de Bloom (1981) aplicados en clases de inglés con estudiantes de sexto grado del colegio IPARM de la Universidad Nacional, Sede Bogotá. Las seis categorías del dominio cognitivo de Bloom (conocimiento, comprensión, aplicación, análisis, síntesis y evaluación) se trabajaron usando actividades de lectura. Para iniciar el trabajo de desarrollo de procesos cognitivos y de habilidades de aprendizaje de inglés, fue necesario comenzar a leer por placer. Los hallazgos –luego de la triangulación de datos a través del diario de las profesoras, la observación y los trabajos elaborados por los estudiantes– evidencian un mejoramiento significativo en el desarrollo de procesos cognitivos y, en general, en las habilidades de aprendizaje de inglés como lengua extranjera. Palabras clave: Procesos cognitivos, estrategias de lectura, taxonomía de Bloom, habilidades de aprendizaje de inglés